Characterization of bacterial community and flavor differences of different types of Douchi. Issue 7 (18th May 2021) - Wang, Yurong; Xiang, Fanshu; Zhang, Zhendong; Hou, Qiangchuan; Guo, Zhuang
Abstract: According to the appearance and technology, traditional fermented Douchi can be divided into dried Douchi and wet Douchi. However, there are few reports on the difference of bacterial community structure between them or the influence of bacterial community on product flavor. In this study, high‐throughput sequencing technology and electronic nose were used to measure the bacterial diversity and flavor of 40 Douchi samples, and the correlation between them was explored by multivariate statistical means combined with COG database. Results showed that the cumulative average relative abundance of Firmicutes and Proteobacteria in the samples was as high as 95.93%, and the former was the core bacteria phylum. On the whole, the dominant bacteria in Douchi were Bacillus (50.67%), Staphylococcus (14.07%), Enterococcus (2.54%), Proteus (1.61%), Brevibacillus (1.46%), Providencia (1.26%), Weissella (1.24%), and Ureibacillus (1.19%). LEfSe analysis indicated that Bacillus can be used as a biomarker in dried fermented soybeans. Meanwhile, dried samples contained more intensive aromatic substances, but were significantly lower in W6S (selectivity to hydrogen) and W3S (methane‐aliph) compared with the wet samples. Aneurinibacillus and Brevibacillus were helpful to the formation of aromatic flavor in Douchi, but Vagococcus and Corynebacterium were the opposite. Gene and microbial phenotypic prediction showed that microorganisms in dried Douchi use protein more efficiently, while in wet Douchi, microbial energy metabolism was more vigorous. The pathogenic potential of microorganisms in dried samples was higher than that in wet. This study can sound the alarm for improving the safety of home‐brewed Douchi and provide guidance for the subsequent screening of strains that enhance the flavor of fermented soybeans. Abstract : Bacillus, Staphylococcus, Enterococcus, Proteus, Brevibacillus, Providencia, Weissella, and Ureibacillus were the dominant bacteria of Douchi; Brevibacillus and Aneurinibacillus had significant positive correlations with three aromatic characteristics but Vagococcus and Corynebacterium were the opposite; Microorganisms in dried Douchi use protein more efficiently, while in wet Douchi, microbial energy metabolism was more vigorous.